2010
DOI: 10.1159/000253864
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Incidence of Pancreatic Cancer-Related Depression and Its Relationship with the Quality of Life of Patients

Abstract: Aim: To investigate the incidence of pancreatic cancer-related depression and the relationship between symptoms of depression and the quality of life (QoL) of patients. Methods: 262 inpatients with cancer of the digestive system (pancreatic cancer, liver cancer, esophageal cancer, gastric cancer, and colorectal cancer) from four Guangzhou hospitals were enrolled into the study between June 2007 and June 2009. The Hamilton Rating Scale for Depression-24 questionnaire was used to assess the degree of depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 39 publications
0
39
1
2
Order By: Relevance
“…Pancreatic cancer is one of the most dismal prognoses among cancers and it was previously reported that patients with pancreatic cancer develop depressive symptoms at high rates (32,33). In addition, whereas patients with esophageal cancer had a high proportion of delirium, this was not mentioned in previous reports and might just have been due to the small number of cases in this study.…”
contrasting
confidence: 58%
“…Pancreatic cancer is one of the most dismal prognoses among cancers and it was previously reported that patients with pancreatic cancer develop depressive symptoms at high rates (32,33). In addition, whereas patients with esophageal cancer had a high proportion of delirium, this was not mentioned in previous reports and might just have been due to the small number of cases in this study.…”
contrasting
confidence: 58%
“…In a comprehensive review, Massie [7] referred to the prevalence of depression in pancreatic cancer between 33 and 50%. Different from the study by Lin et al [3] , some trials performed prior to confirmation of cancer diagnosis observe psychological symptoms preceding somatic disorders [8,9] . Therefore, a discussion about 'mental symptoms as an aid in early diagnosis of pancreatic cancer' was started [10][11][12] .…”
mentioning
confidence: 73%
“…nal cancers were statistically significant [3] . These findings are consistent with the data published so far.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Bu komorbiditenin, hastaların tanıyı bilip bilmemeleri ile ilişkili olmadığı gösterilmiştir (7). Pankreas kanseri ve depresyonun ortak patofizyolojik kökene sahip olduğu öne sürülerek yapılan araştırmalarda, bu düşünceyi destekleyen bulgular elde edilmiştir.…”
Section: Discussionunclassified